Three-dimensional modelling of combustion and emissions characteristics in direct-injection diesel engines using detailed chemistry based on the SAGE combustion model - Medjahed, Lamia; Bousbaa, Hamza; Benramdane, Mohammed; Nor El Houda Hagani, Bouchra (Archives of Thermodynamics, 2026)
This study employed a three-dimensional CFD model with integrated chemical kinetics using CONVERGE CFD software. We used a detailed mechanism of 42 species and 167 reactions and compared its predictions with a reduced 77-species mechanism developed by Liu and Zhang (2023), both tailored for n-heptane oxidation. Validation of diesel-injection combustion was carried out by comparing the model results with experimental engine data. Numerical simulations were conducted on an MKDIR 620-145 engine at 1400 rpm and 50% load. The chosen models reproduced the mean in-cylinder pressure accurately, with deviations below 4.7%. Analysis of species and thermal fields revealed that key intermediate species emerge near 930 K, where H₂O₂ concentrations become sufficient to trigger auto-ignition and the heat release rate reaches its peak. At higher temperatures (around 1300 K), OH and CO concentrations are notably elevated. Soot production is initiated early in combustion and is dominated by diffusion processes; the peak net soot mass was 3.25×10⁻⁷ kg at 18° before the top dead centre. Throughout combustion, CO₂, H₂O and hydrocarbon concentrations increase markedly while O₂ is consumed, with CO₂ and H₂O rising rapidly during both premixed and diffusion combustion phases. NOx formation closely follows the temperature history, approaching a saturation level near 1.1×10⁻⁴ kg under the studied conditions. Overall, the results indicate that the employed reaction mechanisms capture the temporal evolution of combustion, species formation, soot production and emission trends with good fidelity, supporting their suitability for studying fuel behaviour and emissions in diesel engine environments.